Striving for a biopsychosocial approach: A secondary analysis of mutual components during healthcare encounters between women with endometriosis and physicians. Issue 3 (September 2019) - Berterö, Carina; Alehagen, Siw; Grundström, Hanna
Objective: The objective of this study was to identify and describe mutual components during healthcare encounters between women with endometriosis and physicians. Methods: Secondary analysis of data was obtained from two original face-to-face interview studies, one with nine women with endometriosis and one including 16 physicians. Data in this secondary analysis were analysed using thematic analysis. Results: Three themes were identified. (1) Continuity as a foundation for a biopsychosocial approach. The women and the physicians described the importance of continuity and both parties strived for a biopsychosocial approach whereby the female body was not treated as biomedical defect object, but as a part of the unity that constitutes a human being. (2) Listening sensitively. Women and physicians believed that listening sensitively involved more than just hearing the actual words – it required thoughtfulness, reflection and responsiveness. (3) Timing of diagnosis. The physicians tried to protect the women from worrying by treating the painful menstruations without mentioning endometriosis. However, the women regarded not mentioning endometriosis as a lack of competence on the part of the physicians. Conclusion: This study provides new insights into the need for further support in the provision of psychosocial care for women with endometriosis, in the striving towards a biopsychosocial approach.